“Institutionalized States of Information Abstinence”: Cut-up Inquiry of Sex Educators’ Erasure Poems - Hare, Kathleen (Kaye) A. (Art/Research International, 2021)
In this study, I provide applied examples of using cut-up poetic inquiry as an arts-based research method for analyzing erasure poetry. The erasure poetry was composed by five poet-participants and me during a sensory ethnography that explored embodied experiences of a sexual educator training program. I first overview erasure poetics in the context of sexuality education. I explain how erasure poetry as method can interrupt authoritative proclamations of truth, while also providing a technique to grapple with complex, corporeal data – central topics in sex education research. I then theorize cut-up poetic inquiry as an additional form of erasure, asking and illustrating how the processes of cut-up can distill information to enable emergent analytic insights in the context of my research. Throughout, I meditate on how erasure poetry as an arts- based research method can contribute to discussions of language, discourse, and embodiment in sex education research.